Penerapan Pembelajaran Kontekstual Berbasis Limbah Plastik dalam Menanamkan Nilai Kebersihan Lingkungan Islami di Madrasah Ibtidaiyah - Putri, Shilfany (IIQ An Nur Yogyakarta, 2025)
Environmental awareness from a young age is crucial for creating a generation that cares about cleanliness and environmental sustainability. From an Islamic perspective, maintaining cleanliness is part of faith and is a human responsibility to care for the earth as a trust from Allah SWT. However, science learning in Madrasah Ibtidaiyah (MI) tends to focus solely on theory and places less emphasis on direct experience. This study aims to describe the application of contextual learning based on plastic waste to instill Islamic environmental hygiene values in science learning activities. The method used in this study is descriptive qualitative through observation, interviews, and document collection at MIS Bidayatul Hidayah, with the subjects studied being teachers and fourth-grade students. The results indicate that the use of plastic waste as a learning tool can increase ecological awareness, critical thinking skills, and religious responsibility of students in maintaining the cleanliness of the school environment. This study recommends that contextual learning with an Islamic nuance be adopted as an effective strategy to improve scientific literacy, character, and environmental awareness among MI students.